PERAN GLOBAL ALLIANCE FOR VACCINE AND IMMUNIZATION (GAVI) DALAM MENURUNKAN ANGKA KEMATIAN IBU (AKI) DAN ANGKA KEMATIAN BAYI (AKB) DI INDONESIA TAHUN 2011-2015 - Muhammad Raffi Irawan (2021)
This study has the aim of knowing how the role of GAVI in helping to reduce MMR and IMR in Indonesia through the Reprogramming GAVI HSS activities in the 2011-2015 period. Indonesia is one of the countries in the Southeast Asia region stated by WHO as a country that has a high MMR and IMR rates, given that MMR and IMR are one of the problems in the health sector, which is still a severe challenge especially for developing countries in the world and by looking at the fact the two things are indicators in the success of the country's development listed on the MDGs. So to overcome this problem, the Indonesian government conducts several efforts to reduce MMR and IMR in their countries such as one of them by asking for assistance to international organizations, GAVI. The increased of maternal mortality rate and slowing down the decline in infant mortality rate in 2012 in Indonesia which was considered to threaten Health Security, resulting in GAVI issued a policy to carry out the Reprogramming activities of GAVI HSS by conducting a series of activities from increased coverage of immunization, the development of KIA service capacity and increased midwife competency. The method used to achieve the objectives in this study is a descriptive method which is then explained using the framework of role theory, international organizations and the concept of human security. In this study there would be more matters about the role of GAVI as an indpendent instrument and actor in helping to reduce MMR and IMR in Indonesia